1989
DOI: 10.1063/1.344001
|View full text |Cite
|
Sign up to set email alerts
|

Triggering in trigatron spark gaps: A fundamental study

Abstract: The trigatron has been in widespread use as a demand-triggerede high-voltage switch for more than 40 years. In spite sf the poparlarity and maturity of the technology, there persists an uncertainty over the basic physical mechanism (s) responsibIe for triggering breakdown in the devices. We present the results of an ern~BricaZ study OE tadgatrons that directly demonstrates that breakdown is initiated by a streamer launched from the trigger pin, independent of the trigger spark. We compare our results with thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Switching characteristics of electrically triggered gas switches still depend on applied voltage and to ensure good dynamic range and jitter performance, they require fast trigger voltage pulses with amplitude comparable to the switched voltage. 30 This requirement makes such a system impractical. Performance of laser triggered gas switches depends on the properties of the laser trigger pulse.…”
Section: Kv Pulsed Diode Prototype Electron Sourcementioning
confidence: 99%
“…Switching characteristics of electrically triggered gas switches still depend on applied voltage and to ensure good dynamic range and jitter performance, they require fast trigger voltage pulses with amplitude comparable to the switched voltage. 30 This requirement makes such a system impractical. Performance of laser triggered gas switches depends on the properties of the laser trigger pulse.…”
Section: Kv Pulsed Diode Prototype Electron Sourcementioning
confidence: 99%
“…Initially two identical capacitor charged up to the voltage V0. High voltage f fed between trigger pin and corresponding e gap switch [10,11], it will start conducting g starts to flow in the two separate circuits and at load with the direction shown in the figu R 2 , L 2 represents the circuit lead resistan respectively of the two loops and load is rep and L L value. When both switches (S1 an from the equivalent circuit figure, one can w equation…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6][7][8] found that the maingap breakdown time t bd , defined as the time between arrival of the voltage pulse at the trigger pin and appearance of significant current in the main gap, and the associated jitter bd are minimized using a positive trigger pulse and a negative main gap, i.e., the opposite electrode is at negative potential. For 0.5 V sb р͉V g ϪV t ͉ϽV sb , Williams and Peterkin 6 found that the arc formation time t a , defined as the time required after streamer contact with the opposite electrode for the main-gap current to rise to Ͼ95% of the steady-state value, as well as bd are minimized and are least dependent upon trigger pin geometry and dimensions for the same heteropolar configuration. t a and bd increase dramatically when ͉V g Ϫ V t ͉ р 0.7V sb .…”
Section: B Breakdown Time and Jitter Measurementsmentioning
confidence: 99%
“…Two discharge initiation and switch closure mechanisms are possible: [3][4][5][6][7] ͑i͒ if ͉E t ͉ Ͼ͉ E g ͉, then the trigger pulse first causes breakdown to the adjacent electrode ͑BAE͒ and the resulting UV radiation and plasma provide a source of ionization leading to discharge across the main gap, or ͑ii͒ if ͉E t ͉ Ͻ͉ E g ͉, then the trigger pulse first forms breakdown streamers directly to the opposite electrode ͑BOE͒ 8 and the resulting ionization density, which is driven by the applied field, avalanches until the arc channel forms, the resistance across the main gap drops abruptly, and the switch closes. Wells 8 found that the propagation velocity of these streamers is difficult to explain on the basis of conventional models and, therefore, we use the more generic term discharges henceforth.…”
Section: Introductionmentioning
confidence: 99%